Early insights into the neurobiology of pain in sickle cell disease: A systematic review of the literature. Issue 9 (13th May 2015) - Brandow, Amanda M.; Farley, Rebecca A.; Panepinto, Julie A.
<x xml:space="preserve">Abstract</x> Novel insights into the neurobiology of sickle cell disease (SCD) pain have recently been discovered. We systematically reviewed the literature focusing on original research that examined the biology of pain in SCD and/or addressed assessment or treatment of neuropathic pain in SCD. This review of 15 articles that met inclusion criteria provides epidemiological, basic, and clinical data that support central and/or peripheral nervous system abnormalities likely contribute to sickle cell pain. Continued basic and clinical investigation into pain neurobiology is imperative to translate these discoveries into novel ways to assess and treat neuropathic pain and decrease patient suffering. Pediatr Blood Cancer 2015;62:1501–1511. © 2015 Wiley Periodicals, Inc.